2022
DOI: 10.1093/bib/bbac062
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning methods for prediction of cancer driver genes: a survey paper

Abstract: Identifying the genes and mutations that drive the emergence of tumors is a critical step to improving our understanding of cancer and identifying new directions for disease diagnosis and treatment. Despite the large volume of genomics data, the precise detection of driver mutations and their carrying genes, known as cancer driver genes, from the millions of possible somatic mutations remains a challenge. Computational methods play an increasingly important role in discovering genomic patterns associated with … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 131 publications
0
12
0
Order By: Relevance
“…Machine learning is used in many applications for prediction and detection including can-cer driver genes [12]- [14]. There exist review articles covering the details of different methods with the pros and cons of the available methods [15]- [17]. This section presents methods more related to the proposed model.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Machine learning is used in many applications for prediction and detection including can-cer driver genes [12]- [14]. There exist review articles covering the details of different methods with the pros and cons of the available methods [15]- [17]. This section presents methods more related to the proposed model.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It builds analytical models by analyzing existing data, and learns by observations with the primary purpose of making decisions on its own in the future. Models can be trained and automated to analyze multidimensional data for classification, clustering and predictive purposes [26,27]. Classification is a supervised learning approach in machine learning which is used to analyze a dataset provided and construct a model to divide data into a unique set of categories [28].…”
Section: Introductionmentioning
confidence: 99%
“…[12, 13]). Interesting reviews on these methods can be found in [14, 8, 15]. Most current methods for discovering cancer drivers do not consider the temporal information of the disease, nor do they include suitable procedures for testing the causal nature of cancer progression.…”
Section: Introductionmentioning
confidence: 99%